Introducing the Hamiltonian as a 'thermodynamic' potential - Correa V. F.; Correa, Víctor Félix (IOP Publishing, 2019)
Fil: Correa, V. F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina